On the role of ice‐nucleating aerosol in the formation of ice particles in tropical mesoscale convective systems. Issue 3 (4th February 2017) - Ladino, Luis A.; Korolev, Alexei; Heckman, Ivan; Wolde, Mengistu; Fridlind, Ann M.; Ackerman, Andrew S.
Abstract: Over the decades, the cloud physics community has debated the nature and role of aerosol particles in ice initiation. The present study shows that the measured concentration of ice crystals in tropical mesoscale convective systems exceeds the concentration of ice nucleating particles (INPs) by several orders of magnitude. The concentration of INPs was assessed from the measured aerosol particle concentration in the size range of 0.5 to 1 µm. The observations from this study suggest that primary ice crystals formed on INPs make only a minor contribution to the total concentration of ice crystals in tropical mesoscale convective systems. This is found by comparing the predicted INP number concentrations with in situ ice particle number concentrations. The obtained measurements suggest that ice multiplication is the likely explanation for the observed high concentrations of ice crystals in this type of convective system. Key Points: Ice nuclei have minor contribution in the ice initiation in mesoscale convective systems Ice multiplication plays a dominant role in the cloud ice crystal formation in mesoscale convective systems Obtained new data on aerosol concentration near mesoscale convective systems